Nanoencapsulation of natural products and their role in the preservation and control of contaminations in the food industry - RODRIGUES, Sarah de Oliveira; SILVA, João Marcos Oliveira da; BANWO, Kolawole; LIMA, Clara Mariana Gonçalves; GUINÉ, Raquel Pinho Ferreira; VERRUCK, Silvani; PAGNOSSA, Jorge Pamplona (Food Science and Technology, 2024)
Microbial resistance is a problem of high notoriety and importance, being investigated in several scientific areas. Directly correlated to the abuse of macrolides in the pandemic context, the difficulty in eliminating resistant microorganisms and the control of bacterial contamination in an industrial food environment have been increasingly worrying nowadays. The present study demonstrates hypotheses of microbial control using the encapsulation of essential oils and products of natural origin through the technology used in nanocomposites. The aid in the prevention and control of microorganisms with high antimicrobial resistance factors in food industry environments can be seen. Furthermore, new approaches and themes applied in the denaturation of pathogenic biofilms and nanoencapsulation and the use of common metals and transition metals are highlighted.